2005
DOI: 10.1093/ps/84.11.1785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of slower-growing broiler genotypes grown with and without outdoor access: meat quality

Abstract: Consumer interest in organic and natural poultry products raised with outdoor access is growing. An experiment was conducted to assess the effects of outdoor access and genotype on meat quality. One slow-growing genotype (S), 2 medium-growing genotypes (M1 and M2), and a commercial fast-growing genotype (F) were raised (straight-run) for 81, 67, or 53 d, respectively. The placement date was staggered in order to achieve a similar final body weight. Each genotype was assigned to 3 pens of 24 birds each and rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
117
10
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(209 citation statements)
references
References 17 publications
30
117
10
17
Order By: Relevance
“…Also, values of hardness were higher in these animals (5.64 kg) (Franco et al, 2012b). This is noticeable in the present study, as shear force levels were slightly higher than those found for broiler breast meat (Cavitt et al, 2004;Fanatico et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…Also, values of hardness were higher in these animals (5.64 kg) (Franco et al, 2012b). This is noticeable in the present study, as shear force levels were slightly higher than those found for broiler breast meat (Cavitt et al, 2004;Fanatico et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…Differences in meat fat content between genotypes of broiler chickens have also been found and have been attributed to differences in the degree of animal maturity (Fanatico et al, 2005). The protein content of drumstick meat decreased with the age of the capons and correlated with an increase in fat; capons probably stopped protein deposition before the 5 th month.…”
Section: Discussionmentioning
confidence: 97%
“…However, to directly compare the presented data with other studies the colour analysis system has to be considered. In scientific reports that also used the Minolta colorimeter comparable L*a*b* values of the breast muscle had been determined (Cavitt et al, 2004;Young et al, 2004;Fanatico et al, 2005).…”
Section: Discussionmentioning
confidence: 99%